Hemorrhage Risk of Brain Arteriovenous Malformations During Pregnancy and Puerperium in a North American Cohort. Issue 6 (June 2017) - Porras, Jose L.; Yang, Wuyang; Philadelphia, Eunice; Law, Jody; Garzon-Muvdi, Tomas; Caplan, Justin M.; Colby, Geoffrey P.; Coon, Alexander L.; Tamargo, Rafael J.; Huang, Judy
Abstract : Background and Purpose—: Conclusions reached in existing literature about risk of arteriovenous malformation (AVM) hemorrhage during pregnancy are controversial. This study compares the risk of hemorrhage in pregnant and nonpregnant female patients with AVM in a North American cohort. Methods—: We retrospectively reviewed female patients with AVM evaluated from 1990 to 2015. Exposure period for pregnancy and puerperium was calculated as 40 and 6 weeks, respectively, for each full-term pregnancy and 6 weeks for each abortion. Hemorrhage events and patient-years were calculated during an exposure period (pregnancy and puerperium), and a nonexposure period defined as either the interval from birth until AVM obliteration or until last follow-up after subtracting exposure period. Poisson rate ratio test was used to compare rate of hemorrhage between exposure and nonexposure periods. Results—: For 270 female patients with AVM, mean age was 35.0±19.6 years, and race distribution was white (n=165, 61.1%), black (n=59, 21.9%), Hispanic (n=9, 3.3%), Asian (n=6, 2.2%), and other (n=31, 11.5%). From 191 total pregnancies occurring before AVM obliteration, there were 175 (91.6%) term deliveries and 16 (8.4%) abortions. Overall annual hemorrhage rate for 149 total hemorrhages during an average of 11 097 patient-years was 1.34%. There were 140 hemorrhages in nonexposed women and 9 hemorrhages in pregnant women, translating to an annual hemorrhage rate of 1.3% in nonpregnant women versus 5.7% in pregnant women ( P <0.001). Identical analysis for reproductive age patients (15–50) demonstrated a rate of 1.3% versus 7.0% ( P <0.001). Conclusions—: Our results conflict with those from a recent study describing no increased rate of rupture during pregnancy. This difference may reflect unique population attributes influencing brain AVM hemorrhage during pregnancy. Abstract : Supplemental Digital Content is available in the text.